IDENTIFIKASI DRUG RELATED PROBLEMS (DRPS) PADA PASIEN ANAK DEMAM BERDARAH DENGUE (DBD) DI INSTALASI RAWAT INAP RSUD UNDATA PALU TAHUN 2011 - Rizky, Moh Zainal; Mukaddas, Alwiyah; Faustine, Inggrid (Univ. Tadulako, 2014)
Drug Related Problems (DRPs) is an unexpected incident patients experience consequences or unforeseen consequences could potentially interfere with drug therapy to therapy outcomes. Dengue Hemorrhagic Fever (DHF) is one of diseases that occur in children and have a great chance to be the occurrence of DRPs. This study aims to find out the extent of potential DRPs in the incidence of DHF in children patients at the RSUD (public hospital) Undata Palu. This research was non experimental study using a descriptive retrospective study. The research was conducted by collecting data from the medical records of children patient (1-12 years old) undiagnosed DHF at RSUD Undata Palu. The data analyzed includes unnecessary drug therapy, wrong medicine, subtherapy dose and overdose. Based on the results of the study, we obtained that from 103 patients who met the criteria there were total of around 171 cases of DRPs cases, i.e. 103 cases (57.89%) was clasified as unnecessary drug therapy category, 25 cases (14,62%) was categorised as wrong medicine, 39 cases (22,81%) was over dose categories, and 8 cases (4,68%) was subtherapy dose category. The most often DRPs incidents occurs in this study were unnecessary drug therapy should be as large as 57,89 % of the total cases of DRPs.